Corporations as criminals problems and progress in the Philippine Law (2021)
In the Philippines, corporations are important economic actors. Yet, when they commit crimes through the acts of their agents, they remain virtually exempt from prosecution: prosecutors are not guided by uniform rules in investigating and charging corporations, there are no clear procedural rules that guide courts in trying corporations as criminal defendants, and there is scarcity of authorities that categorically identify the rights protections afforded to accused corporations. This Note identifies the laws that impute corporate criminal liability, evaluates the current state of procedural rules as they relate to corporate defendants, and analyzes textually, historically, and comparatively the constitutional provisions that afford protections to those accused of committing crimes. Clarity in how corporations are investigated, prosecuted, and tried leads to a stable and consistent application of criminal law, ensures a level playing field for businesses, and contributes to the promotion of the rule of law in the Philippines.
Keywords: Corporations -- Corrupt practices; Criminal liability; Philippine Politics